2020
DOI: 10.1101/2020.03.26.009969
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tissue interactions govern pattern formation in the posterior lateral line of medaka

Abstract: 1 Vertebrate organs are arranged in a stereotypic, species-specific position along the animal body 2 plan. Substantial morphological variation exists between related species, especially so in the vastly 3 diversified teleost clade. It is still unclear how tissues, organs and systems can accommodate such 4 diverse scaffolds. Here, we use the sequential formation of neuromasts in the posterior lateral line 5 (pLL) system of medaka fish to address tissue-interactions defining a pattern. We show that the 6 pLL pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 76 publications
1
4
0
Order By: Relevance
“…Taken together, these data suggest that there are mechanisms that act specifically post-embryonically to shape pLL patterns and organ numbers, as has been previously suggested for other species (Nuñez et al, 2009;Pichon and Ghysen, 2004). But they also reveal that the origin of differences in patterning in certain cases can be traced back to differences during embryonic development (Seleit et al, 2017a(Seleit et al, , 2022. The genetic basis of those differences remains to be elucidated, but our results uncover a diversity of pLL patterns that is encoded at the level of developmental processes in Oryzias species and strains.…”
Section: Embryonic Pllsupporting
confidence: 79%
See 1 more Smart Citation
“…Taken together, these data suggest that there are mechanisms that act specifically post-embryonically to shape pLL patterns and organ numbers, as has been previously suggested for other species (Nuñez et al, 2009;Pichon and Ghysen, 2004). But they also reveal that the origin of differences in patterning in certain cases can be traced back to differences during embryonic development (Seleit et al, 2017a(Seleit et al, , 2022. The genetic basis of those differences remains to be elucidated, but our results uncover a diversity of pLL patterns that is encoded at the level of developmental processes in Oryzias species and strains.…”
Section: Embryonic Pllsupporting
confidence: 79%
“…Intrigued by the differences observed in the adult pLL patterns among Oryzias species and strains, we decided to look at pLL patterns at the end of embryogenesis, using a number of representative species to gain a better understanding of the origin of those differences. We had previously reported that different embryonic pLL patterns exist in different teleost species (Seleit et al, 2017a(Seleit et al, , 2022, but whether they also differ within the Oryzias clade had not been addressed before. We analysed the final embryonic pLL pattern by looking at recently hatched larvae (N=10 for each species), within 24 h of exiting the chorion, and we noticed two different scenarios.…”
Section: Embryonic Pllmentioning
confidence: 99%
“…To mimic the lack of cxcr4b in mature organs and in a cell-type specific manner, we used the K15 promoter to drive expression of the Cxcr7 receptor, a non-signaling (sinking) receptor that competes with Cxcr4b for the Cxcl12 ligand (Aman & Piotrowski, 2008;Dona et al, 2013;Naumann et al, 2010). Although specific for neural stem cells in the mature neuromast, the K15 promoter drives expression at earlier stages, after primary neuromasts were deposited by the primordium (Seleit et al, 2022). As expected for the over-expression of a functional Cxcr7, Tg(K15::Cxcr7) juveniles often lack secondary embryonic neuromasts, which depend on a proper chemokine signaling (Seleit et al, 2017) (Fig.…”
Section: Chemokine Signaling Modulates Organ-founder Stem Cell Migrationmentioning
confidence: 86%
“…Animal experiments were conducted according to European Union animal welfare guidelines. The published transgenic lines used in this study are : Tg(Eya1:mCFP), Tg(Eya1:EGFP) (Seleit et al, 2017), Tg(K15:H2B-RFP), Tg(K15:H2B-EGFP) (Seleit, Krämer et al, 2017), Tg(K15:LifeAct-tagRFP) (Seleit et al, 2022). Tg(Kremen1:mYFP) was generously provided by J. Wittbrodt's lab.…”
Section: Fish Maintenancementioning
confidence: 99%
See 1 more Smart Citation